208 Immune checkpoint inhibitor-related neurotoxicity: a case series. Issue 12 (14th November 2019) - Brown, Rachel; Au, Lewis; Spain, Lavinia; Furness, Andrew; Rees, Jeremy; Rossor, Alex; Morris, Emma; Zandi, Michael; Lunn, Michael; Larkin, James; Turajlic, Samra; Carr, Aisling
Abstract : Immune checkpoint inhibitors (ICI), monoclonal antibodies enhancing T cell responses against tumour cells, have revolutionised the treatment of cancers such as advanced melanoma, leading to enhanced survival. Their action, however, is not tumour-specific, and patients can develop multisystem immune related adverse events (irAE). Neurological irAEs have been reported in 1–14% of patients, depending upon the ICI used, and can affect any part of the neuro-axis. A recent case series from the Royal Marsden Hospital (RMH) identified 10 patients with neurotoxicity following ICI for advanced melanoma between 2010–15, specifically neuropathy (6), plexopathy (1) and aseptic meningitis (3). Exactly how neurological injury occurs, whether cell-, cytokine- or antibody-mediated, is unknown. We present early data from a newly established collaboration with RMH, aiming to clinically characterize these patients, and identify the cause of neurological injury. To date, we have advised on patients (age range 53–80) with myositis, Guillain-Barré (GBS)-like neuropathy, plexopathy, aseptic meningitis, and encephalitis following ICI (ipilimumab and/or nivolumab) for advanced melanoma. Features common to these patients include their subacute onset, time from ICI administration, and steroid responsiveness (including in GBS-like cases). The incidence of neurological irAEs following ICI will rise with increasing use, and is therefore of concern to practicing neurologists.